ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI RISK MANAGEMENT DISCLOSURE (Studi Kasus Pada Organisasi Manufaktur Sektor Industri Barang Konsumsi Yang Terdaftar Di Bursa Efek Indonesia Periode 2019-2021) - Jessica Claudia; Dewi Fiorentina; Catherine Catherine; Namira Ufrida Rahmi; Putri Keumala Dewi Lubis (Sekolah Menengah Kejuruan (SMK) Pustek, 2023)
The purpose contained in this study is to understand the effect of public ownership, audit committee ownership, auditor reputation, leverage and organizational size on risk management disclosure with case studies on companies in the 2019-2021 period listed on the Indonesia Stock Exchange in Manufacturing in the Consumer Goods Industry. The Indonesian Stock Exchange will be the object of this research. During June 2022-April 2023 this research will take place. This approach applies a quantitative approach, a quantitative approach is a positivism-based system that is used to study certain populations and samples. The population used is companies in the 2019-2021 period which are listed on the Indonesia Stock Exchange in Manufacturing in the Consumer Goods Industry as many as 44 companies. There were 27 companies obtained in 3 years of observation from the results of selecting the sample criteria so that a sample of 81 research samples was obtained. The results of this study prove that simultaneously Public Ownership, Audit Committee Ownership, Auditor Reputation, Leverage and Company Size have a significant effect on Risk Management Disclosure. Partially, public ownership, audit committee ownership, and company size have a significant effect, but auditor reputation and leverage have no effect.